Transport Policies and Development - Berg, Claudia N. (World Bank, Washington, DC, 2015)
This survey reviews the current state of the economic literature, assessing the impact of transport policies on growth, inclusion, and sustainability in a developing country context. The findings are summarized and methodologies are critically assessed, especially those dealing with endogeneity issues in empirical studies. The specific implementation challenges of transport policies in developing countries are discussed.